The physiology of world class sprint skiers - Sandbakk, O.; Leirdal, S.; Holmberg, H. C.; Ettema, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
During sprint competitions in cross-country skiing, athletes perform four separate races of 1200-1800m (2 to 4 min), starting with a time-trial qualification race, and thereafter heats based on a knock-out system. In order to better understand world class sprint performance, the present study investigated the differences between world class and national class sprint skiers with regard to their physiological characteristics. Methods: Eight world class (26.1±3.5 yr, 184.8±5.6 cm, 83.3±6.4 kg, sprint FIS-points 22.2±12) and eight national class (24.5±2.3 yr, 186.4±6.6cm, 82.8±6.6 kg, sprint FIS-points 100.6±45.6) sprint skiers participated in the study. They performed three standardized tests using the freestyle V-2 technique while roller skiing on a treadmill: 1) an absolute submaximal velocity test, 2) an incremental peak aerobic capacity (VO2peak) test, and 3) an incremental treadmill velocity test, leading to a maximal obtainable speed after 60-90s (Vmax). Moreover, all the subjects performed 30m acceleration and 30m maximal speed tests in the skating V-2 technique outdoors on an asphalt road. Additionally, the amount of training was quantified for different intensity zones, from low intensity endurance training to strength and speed training, according to training logbook entries. Comparisons between groups were made using the t-test procedure. Results: World class athletes showed significantly lower blood lactate levels, respiratory exchange ratio and heart rate, as well as better gross efficiency, at the submaximal velocity (all P<0.05). Furthermore, they had higher VO2peak, speed at VO2peak, Vmax-speed, and faster lactate clearance after the Vmax (all P<0.05). No differences in acceleration, maximal speed and peak lactate levels were found. World class athletes performed more endurance training and speed training (P<0.05). Discussion: World class sprint skiers are similar to national class sprint skiers as regards maximal speed and acceleration. However, they are superior in aerobic capacity, efficiency and lactate clearance. Among sprint skiers, we hypothesize that a certain level of speed is needed, however, the aerobic characteristics are what differentiates different performance levels. It is suggested that national class athletes with already high speed capacities should increase their emphasis on endurance training to further improve sprint performance.